Primary Intracranial Myoepithelial Neoplasm: A Potential Mimic of Meningioma. (May 2016) - Choy, Bonnie; Pytel, Peter
Myoepithelial neoplasms were originally described in the salivary glands but their spectrum has been expanding with reports in other locations, including soft tissue. Intracranial cases are exceptionally rare outside the sellar region where they are assumed to be arising from Rathke pouch rests. Two cases of pediatric intracranial myoepithelial neoplasm in the interhemispheric fissure and the right cerebral hemisphere are reported here. Imaging studies suggest that the second case was associated with cerebrospinal fluid dissemination. Both cases showed typical variation in morphology and immunophenotype between more epithelioid and more mesenchymal features. The differential diagnosis at this particular anatomic location includes meningioma, which can show some overlap in immunophenotype since both tumors express EMA as well as GLUT1. One case was positive for EWSR1 rearrangement by fluorescence in situ hybridization. One patient is disease free at last follow-up while the other succumbed to the disease within days illustrating the clinical spectrum of these tumors.